Bilateral multi-issue negotiation of execution contexts by proactive document agents. (14th October 2019) - Kaczorek, Jerzy; Wiszniewski, Bogdan
A proactive document can react to its actual environment by autonomously selecting and performing actions integrated into its body and interact with its user. When migrating over a network of execution devices it may encounter diverse execution contexts, each one set up according to temporal characteristics of a receiving device and preferences of its owner. A concept to augment proactive documents with negotiation capability is proposed - to make them responsive to such dynamically changing contexts, and implemented in a system, where they can migrate as attachments to e-mail messages, owing to a dedicated e-mail client capable of handling them. Negotiation is based on a simple game-theoretic mechanism to minimise computation load on execution devices. Four negotiation algorithms are proposed and two of them evaluated in more detail in a series of experiments, when respectively, negotiating parties do not or do have knowledge on past encounters and negotiated contracts.